The Effects of Information and Incentive Interventions on the Adoption of Algorithms in Human Resources: An Experimental Study - Ochmann, Jessica; Zilker, Sandra; Michels, Leonard; Tiefenbeck, Verena; Matzner, Martin; Laumer, Sven (Data Base for Advances in Information Systems, 2025)
The economic potential of human resources (HR) algorithms requires organizations to ensure their adoption, but HR employees are often reluctant to use them. One driver of this reluctance may be employees’ overconfidence in their own judgments and the sensitive nature of HR decisions, which directly affect human beings. Interventions that aim to increase technology adoption can help organizations overcome this issue. Drawing on the theoretical lens of information and incentive interventions, we conducted a survey-based incentive-compatible online experiment with 276 participants to determine the effects of interventions on the adoption of algorithms in an organizational HR context. We distinguish between adoption in the short and long runs. Our study, which contributes to research on the use of algorithms in HR and induced technology adoption, has practical implications for HR leaders who seek to increase HR employees’ adoption of algorithms in completing HR-related tasks.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Algorithm; Human Resources; Incentive; Information; Recruiting